Evaluation of Dental Advice Delivery: A Comparative Study of General Practitioners and Specialists in Benghazi. - Budajaja, Hunaida; Abraheem, Mubarakah; Gaber, Amal; Ahmadi, Osama; Fathallah Benghasheer, Hala (Scientific Journal of University of Benghazi, 2025)
Oral health education is a crucial aspect of dental care, as proper guidance from dentists can significantly influence patients’ oral hygiene habits. This study investigated whether dentists in Benghazi provide dental advice to patients and examined differences between general practitioners (GPs) and specialists in delivering such advice. This cross-sectional study included 246 dentists from public clinics and the Faculty of Dentistry at the University of Benghazi. Data were collected through a structured questionnaire covering sociodemographic details, oral health practices, and advice given to patients. Analysis was conducted using IBM SPSS version 24, employing descriptive statistics and chi-square tests to compare GPs and specialists. Results showed that both GPs and specialists consistently provided oral hygiene and smoking-related advice, with no significant difference (p > 0.05). GPs (68.2%) were slightly more likely to offer preventive advice than specialists (62.9%), while specialists (85.4%) provided dietary advice more frequently than GPs (75.2%), though these differences were not significant (p > 0.05). However, a significant difference was observed in professional treatment advice, with 98.9% of specialists providing it compared to 92.4% of GPs (p = 0.028). These findings highlight the need for standardized preventive care strategies to enhance patient education and oral health outcomes. However, the inconsistent advice provided by dentists may be due to insufficient training in preventive care and the treatment-oriented nature of Libya’s dental health system.